Perovskite battery based on NIC interface modification and preparation method thereof

CN117560934BActive Publication Date: 2026-10-27HENAN UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311699166.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-12
Publication Date
2026-10-27
Estimated Expiration
2043-12-12

AI Technical Summary

Technical Problem

而钙钛矿结晶过程较为复杂、目前没有完美的策略控制钙钛矿结晶过程

Benefits of technology

[0012]本发明具有以下有益效果:本发明提供一种简单的方法得到NIC钝化的钙钛矿电池。利用该方法可获得大晶粒的高质量钙钛矿薄膜,同时基于NIC钝化层的钙钛矿太阳能电池性能优异,光电转换效率高。另外,NIC钝化了二氧化钛的表面氧空位缺陷,且与钙钛矿之间形成配位键,促进高质量钙钛矿薄膜的形成。该发明为钙钛矿太阳能电池商业化提供切实可行的思路和方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117560934B_ABST
    Figure CN117560934B_ABST
Patent Text Reader

Abstract

The application discloses a perovskite cell based on NIC (nicotinic acid-3-formamide) interface modification and a preparation method thereof, and belongs to the technical field of perovskite solar photovoltaic technology. The perovskite cell device is composed of a transparent conductive glass, an electron transport layer, a NIC modification layer, a perovskite light absorption layer, a hole transport layer and a counter electrode in sequence. (1) The FTO conductive glass is ultrasonically cleaned and then treated by plasma to obtain a clean substrate; (2) a TiO2 dense layer is prepared on the clean substrate; (3) a TiO2 mesoporous layer is prepared on the TiO2 dense layer; (4) a NIC modification layer is prepared by spin coating on the TiO2 mesoporous layer; (5) a perovskite light absorption layer is spin coated on the modification layer; (6) a Spiro-OMeTAD precursor solution is spin coated on the perovskite layer to obtain a hole transport layer; and (7) after the hole transport layer is oxidized, a Ag counter electrode is vacuum evaporated on the hole transport layer to obtain a NIC interface modified perovskite solar cell. The device preparation process is simple, the cost is low, the prepared NIC interface modified perovskite cell has excellent performance, and the photoelectric conversion efficiency is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of perovskite solar photovoltaics, specifically relating to a perovskite cell based on NIC interface modification and its preparation method. Background Technology

[0002] Perovskite solar cells are a disruptive photovoltaic technology that has emerged in recent years. Compared to traditional silicon solar cells, perovskite cells offer a range of advantages, including lighter weight, greater flexibility, and high-throughput fabrication via solution methods. In terms of efficiency alone, silicon-based solar cells have achieved an efficiency of 26.8% after more than 70 years of development, while perovskite solar cells have reached 26% efficiency in just 14 years, demonstrating their immense development potential and commercial value. However, perovskite solar cells still face many challenges in their commercialization process, such as poor stability in water and oxygen, and low efficiency in large-area devices. Common strategies for improving the performance of perovskite solar cells include interface passivation, component doping, and optimization of solvent or thin-film fabrication processes. Large-size perovskite grains are generally considered fundamental for obtaining high-quality perovskite thin films and high-performance perovskite solar cell devices. However, the perovskite crystallization process is complex, and currently there is no perfect strategy to control it. Interface passivation is a crucial means of influencing the perovskite crystallization process. Furthermore, interface passivation helps improve charge classification and transport processes between perovskite and other functional layers. Introducing a passivation material between the electron transport layer and the perovskite effectively suppresses interfacial carrier recombination and induces perovskite crystallization, which is beneficial for the formation of large-sized perovskite grains. In this application, the introduction of the NIC interfacial passivation layer not only passivates oxygen vacancy defects on the surface of the titanium dioxide electron transport layer but also promotes the formation of high-quality perovskite thin films, ultimately resulting in a perovskite solar cell with excellent performance. Summary of the Invention

[0003] The present invention aims to provide a perovskite solar cell based on NIC interface modification and its preparation method. A simple spin-coating method is used to coat NIC material between titanium dioxide and perovskite to form a passivation layer. This not only reduces oxygen vacancy defects on the titanium dioxide surface and inhibits interfacial carrier recombination, but also allows NIC to form coordination bonds with the perovskite, delaying the perovskite crystallization process and promoting the formation of large-grain perovskite, ultimately resulting in a high-quality perovskite thin film and a high-performance perovskite solar cell. The amino and carbonyl groups in the NIC molecule coordinate with lead or halide ions coordinated at the mid-positions of the perovskite. The formation of these coordination bonds slows down the perovskite crystallization rate, thereby promoting perovskite grain growth and forming a high-quality perovskite thin film with fewer grain boundary defects.

[0004] To achieve the above objectives, the present invention is implemented through the following technical solution: A method for fabricating perovskite solar cells based on NIC interface modification is as follows: (1) The FTO conductive glass was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water in sequence, and then dried with nitrogen to obtain a clean FTO conductive substrate. (2) A solution of titanium acetylacetonate in n-butanol was spin-coated onto a clean FTO conductive substrate, and after annealing, a dense TiO2 layer was obtained. (3) Dilute TiO2 slurry with anhydrous ethanol to obtain TiO2 slurry dilution solution, spin coat TiO2 slurry dilution solution onto TiO2 dense layer, and after annealing treatment, obtain TiO2 mesoporous layer; (4) Spin-coating an ethanol solution of NIC onto a TiO2 mesoporous layer and annealing it to obtain a NIC-modified layer. The preparation process of the ethanol solution of NIC is as follows: dissolve NIC (pyridine-3-carboxamide) in ethanol to obtain an ethanol solution with a concentration of 0.05~5 mg / mL of NIC. (5) CH3NH3I and PbI2 are dissolved in a mixed solution of solvents DMF and DMSO to form a perovskite precursor liquid, which is then spin-coated onto a TiO2 mesoporous layer. During the spin-coating process, anhydrous diethyl ether is added as an anti-solvent. After spin-coating, the mixture is heated on a hot plate to obtain a perovskite light-absorbing layer. (6) Spiro-OMeTAD and additives were dissolved in chlorobenzene and spin-coated onto the perovskite light-absorbing layer to obtain a hole transport layer; (7) The sample was placed in a desiccator for oxidation for 8-24 hours, and Ag counter electrode was vacuum deposited on the hole transport layer to obtain NIC interface modified perovskite solar cell.

[0005] Specifically, in step (1), the ultrasonic cleaning time is 15 minutes in each of the acetone, anhydrous ethanol, and deionized water.

[0006] Further, in step (2), the concentration of the acetylacetone titanium n-butanol solution is 0.1–0.5 mol / L. The spin-coating speed is 1000–3000 rpm, and the spin-coating amount of the acetylacetone titanium n-butanol solution is 15–20 μL / cm. 2 The annealing temperature is 80–150℃, and the annealing time is 5–30 minutes.

[0007] Further, in step (3), the TiO2 slurry is the commercial 18NR-T slurry, and the TiO2 slurry is mixed with anhydrous ethanol at a mass ratio of 1:(4-10) until homogeneous. The spin coating speed is 3000-5000 rpm, and the spin coating amount of the TiO2 slurry dilution is 20-30 μL / cm. 2 The annealing temperature is 450–550℃, and the annealing time is 50–70 minutes.

[0008] Furthermore, in step (4), the spin-coating amount of the NIC ethanol solution is 10~15 μL / cm. 2 The spin coating rate is 500~3000 rpm, the annealing temperature is 90~110℃, and the annealing time is 10~15 minutes.

[0009] Further, in step (5), the concentration of CH3NH3I in the mixed solution is 1 mol / L, and the concentration of PbI2 is 1.05 mol / L. The volume ratio of DMF to DMSO in the mixed solvent is 4:1. The spin-coating amount is 15~20 μL / cm. 2 The spin coating speed is 3000~5000 rpm, the antisolvent is added 10 seconds after the start of spin coating, and the amount of antisolvent is 25~125 μL / cm. 2 The temperature of the spin coating followed by heating on a hot plate is 80~150℃.

[0010] Further, in step (6), the Spiro-OMeTAD precursor solution is obtained by mixing 72.3 mg of Spiro-OMeTAD powder, 28.8 μL of 4-tert-butylpyridine, and 17.5 μL of Li-TFSI salt solution per 1 mL of chlorobenzene. The Li-TFSI salt solution is an acetonitrile solution of Li-TFSI with a concentration of 500 mg / mL. The spin-coating amount of the Spiro-OMeTAD precursor solution is 15~20 μL / cm. 2 The spin coating speed is 3000~5000 rpm, and the time is 30 seconds.

[0011] Furthermore, in step (7), the humidity of the dryer does not exceed 10%. During vacuum evaporation, the vacuum level inside the cavity does not exceed 1*10. -4 Pa.

[0012] This invention offers the following advantages: It provides a simple method for obtaining NIC-passivated perovskite solar cells. This method yields high-quality perovskite films with large grains, and the perovskite solar cells based on the NIC passivation layer exhibit excellent performance and high photoelectric conversion efficiency. Furthermore, NIC passivates the surface oxygen vacancy defects of titanium dioxide and forms coordination bonds with the perovskite, promoting the formation of high-quality perovskite films. This invention provides a practical approach and method for the commercialization of perovskite solar cells. Attached Figure Description

[0013] Figure 1 This is a schematic diagram of the structure of a NIC-modified perovskite solar cell; Figure 2 Efficiency graph of the perovskite solar cell prepared in Example 1; Figure 3 Efficiency graph of the perovskite solar cell prepared in Example 2; Figure 4 Efficiency graph of the perovskite solar cell prepared in Comparative Example 1. Detailed Implementation

[0014] The technical solution of the present invention will be further described in detail below with reference to specific embodiments and accompanying drawings, but the scope of protection of the present invention is not limited thereto.

[0015] Example 1: A method for fabricating perovskite-based solar cells, the process of which is as follows: (1) Cleaning of FTO conductive substrate. The FTO glass was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 15 min each, and then dried with nitrogen gas for later use. (2) Preparation of dense TiO2. The precursor solution is a 0.1M titanium acetylacetonate n-butanol solution. Take 70 μL of this solution and drop it onto the FTO (2cm*2cm) from step (1) to make the solution cover the entire FTO surface. Spin coat at 1500 rpm for 30s, and then dry on a hot plate at 100℃ for 10min to obtain a dense TiO2 layer with a thickness of 35nm. (3) Preparation of TiO2 porous layer. Commercially available TiO2 slurry 18NR-T was diluted with anhydrous ethanol at a mass ratio of 1:7.5. 100 μL of TiO2 slurry dilution was dropped onto the dense TiO2 layer, spin-coated at 5000 rpm for 30 s, dried on a hot plate at 125℃ for 5 min, and then sintered at 450℃ for 60 min to form a 370 nm thick TiO2 mesoporous layer; (4) Preparation of the perovskite light-absorbing layer. 0.483 g of PbI2 and 0.159 g of MAI (CH3NH3I) were dissolved in a mixed solution of 0.2 mL DMSO and 0.8 mL DMF and stirred thoroughly. 75 μL of the perovskite precursor solution was dropped onto the FTO / TiO2 dense layer / TiO2 mesoporous layer substrate and spin-coated at 4000 rpm for 50 s. At the 10th s, 120 μL of diethyl ether antisolvent was added. The perovskite precursor film was obtained and then annealed on a hot plate at 100 °C for 30 min to obtain a perovskite film with a thickness of 400 nm. (5) Preparation of Spiro-OMeTAD hole transport layer. The Spiro-OMeTAD precursor solution was prepared by mixing 72.3 mg of Spiro-OMeTAD powder, 28.8 μL of 4-TBP, and 17.5 μL of Li-TFSI salt solution in 1 mL of chlorobenzene. The Li-TFSI salt solution was an acetonitrile solution of Li-TFSI with a concentration of 500 mg / mL. 70 μL of Spiro-OMeTAD precursor solution was dropped onto the perovskite film from step (4), and the spin coating was performed at a speed of 4000 rpm for 30 seconds. After air drying, a hole transport layer with a thickness of 150 nm was obtained.

[0016] (6) Place the sample obtained in (5) in a desiccator (the humidity of the desiccator does not exceed 10%) and oxidize at room temperature for 10 hours.

[0017] (7) Preparation of Ag counter electrode. Vacuum evaporation was performed on the Spiro-OMeTAD hole transport layer (the vacuum degree in the cavity during vacuum evaporation was no greater than 1*10). -4 A 120 nm thick Ag electrode (Ag electrode area is 0.09 cm²) was constructed. 2 A complete perovskite solar cell was obtained. At AM1.5, 100 mW / cm² 2 Under standard light intensity, such as Figure 2 As shown, the open-circuit voltage of the solar cell sample is 1.07V, and the short-circuit current density is 23.83 mA / cm². 2 The fill factor is 0.79 and the photoelectric conversion efficiency is 20.14%.

[0018] Example 2: A method for fabricating perovskite solar cells based on NIC interface modification is as follows: (1) Cleaning of FTO conductive substrate. The FTO glass was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 15 min each, and then dried with nitrogen gas for later use. (2) Preparation of dense TiO2. The precursor solution is a 0.1M titanium acetylacetonate n-butanol solution. Take 70 μL of this solution and drop it onto the FTO (2cm*2cm) from step (1) to make the solution cover the entire FTO surface. Spin coat at 1500 rpm for 30s, and then dry on a hot plate at 100℃ for 10min to obtain a dense TiO2 layer with a thickness of 35nm. (3) Preparation of TiO2 porous layer. Commercially available TiO2 slurry 18NR-T was diluted with anhydrous ethanol at a mass ratio of 1:7.5. 100 μL of TiO2 slurry dilution was dropped onto the dense TiO2 layer, spin-coated at 5000 rpm for 30 s, dried on a hot plate at 125℃ for 5 min, and then sintered at 450℃ for 60 min to form a 370 nm thick TiO2 mesoporous layer; (4) Preparation of NIC modified layer. The concentration of NIC ethanol solution is 0.15 mg / mL. Take 50 μL of the solution and drop it onto the TiO2 mesoporous layer in step (3). Spin coat at 1000 rpm for 30 seconds. After spin coat, heat on a hot plate at 100°C for 10 minutes.

[0019] (5) Preparation of the perovskite light-absorbing layer. 0.483 g of PbI2 and 0.159 g of MAI (CH3NH3I) were dissolved in a mixed solution of 0.2 mL DMSO and 0.8 mL DMF and stirred thoroughly. 75 μL of the perovskite precursor solution was dropped onto the NIC-modified layer in step (4), and the mixture was spin-coated at 4000 rpm for 50 s. At the 10th s, 120 μL of diethyl ether antisolvent was added. The perovskite precursor film was obtained, and then annealed on a hot plate at 100 °C for 30 min to obtain a perovskite film with a thickness of 400 nm. (6) Preparation of Spiro-OMeTAD hole transport layer. The Spiro-OMeTAD precursor solution was prepared by mixing 72.3 mg of Spiro-OMeTAD powder, 28.8 μL of 4-TBP, and 17.5 μL of Li-TFSI salt solution in 1 mL of chlorobenzene. The Li-TFSI salt solution was an acetonitrile solution of Li-TFSI with a concentration of 500 mg / mL. 70 μL of the Spiro-OMeTAD precursor solution was dropped onto the perovskite film from step (5), and the spin coating was performed at a speed of 4000 rpm for 30 seconds.

[0020] (7) Place the sample obtained in (6) in a desiccator (the humidity of the drying oven does not exceed 10%) and oxidize at room temperature for 10 hours.

[0021] (8) Preparation of Ag counter electrode. Vacuum evaporation was performed on the Spiro-OMeTAD hole transport layer (the vacuum degree in the cavity during vacuum evaporation was no greater than 1*10). -4 A 120 nm thick Ag electrode (Ag electrode area is 0.09 cm²) was constructed. 2 A fully NIC-modified perovskite solar cell was obtained. The cell structure is as follows. Figure 1 As shown, from bottom to top, the layers are FTO, TiO2 dense layer, TiO2 mesoporous layer, NIC modified layer, perovskite light-absorbing layer, hole transport layer and Ag counter electrode.

[0022] At AM1.5, 100 mW / cm 2 Under standard light intensity, such as Figure 3 As shown, the open-circuit voltage of the solar cell sample is 1.11V, and the short-circuit current density is 24.86 mA / cm². 2 The fill factor is 0.82 and the photoelectric conversion efficiency is 22.63%.

[0023] Comparative Example 1: A method for preparing a NIC-doped perovskite solar cell, the process of which is as follows: (1) Cleaning of FTO conductive substrate. The FTO glass was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 15 min each, and then dried with nitrogen gas for later use. (2) Preparation of dense TiO2. The precursor solution is a 0.1M titanium acetylacetonate solution in n-butanol. 70 μL of this solution is taken and dropped onto the FTO in step (1) to make the solution cover the entire FTO surface. The spin coating speed is 1500 rpm and the time is 30 s. Then, it is dried on a hot plate at 100℃ for 10 min to obtain a dense TiO2 layer with a thickness of 35 nm. (3) Preparation of TiO2 porous layer. Commercially available TiO2 slurry 18NR-T was diluted with anhydrous ethanol at a mass ratio of 1:7.5. 100 μL of TiO2 slurry dilution was dropped onto the dense TiO2 layer, spin-coated at 5000 rpm for 30 s, dried on a hot plate at 125℃ for 5 min, and then sintered at 450℃ for 60 min to form a 370 nm thick TiO2 mesoporous layer; (4) Preparation of NIC-doped perovskite light-absorbing layer. 0.483 g of PbI2 and 0.159 g of MAI (CH3NH3I) were dissolved in a mixed solution of 0.2 mL DMSO and 0.8 mL DMF and stirred thoroughly. Then, 1.22 mg of NIC was added and stirred thoroughly again. 75 μL of NIC-doped perovskite precursor solution was dropped onto the FTO / TiO2 dense layer / TiO2 mesoporous layer substrate and spin-coated at 4000 rpm for 50 s. At the 10th s, 120 μL of diethyl ether antisolvent was added. The perovskite precursor film was obtained and then annealed on a hot plate at 100 °C for 30 min to obtain a perovskite film with a thickness of 400 nm. (5) Preparation of Spiro-OMeTAD hole transport layer. The Spiro-OMeTAD precursor solution was prepared by mixing 72.3 mg of Spiro-OMeTAD powder, 28.8 μL of 4-TBP, and 17.5 μL of Li-TFSI salt solution in 1 mL of chlorobenzene. The Li-TFSI salt solution was an acetonitrile solution of Li-TFSI with a concentration of 500 mg / mL. 70 μL of Spiro-OMeTAD precursor solution was dropped onto the perovskite film in step (4), and the spin coating speed was 4000 rpm for 30 seconds.

[0024] (6) Place the sample obtained in (5) in a desiccator (the humidity of the desiccator does not exceed 10%) and oxidize at room temperature for 10 hours.

[0025] (7) Preparation of Ag counter electrode. Vacuum evaporation was performed on the Spiro-OMeTAD hole transport layer (the vacuum degree in the cavity during vacuum evaporation was no greater than 1*10). -4 A 120 nm thick Ag electrode (Ag electrode area is 0.09 cm²) was constructed. 2 A fully NIC-modified perovskite solar cell was obtained. At AM1.5, 100 mW / cm² 2 Under standard light intensity, such as Figure 4 As shown, the open-circuit voltage of the solar cell sample is 1.08V, and the short-circuit current density is 24.01 mA / cm². 2 With a fill factor of 0.80, the photoelectric conversion efficiency is 20.74%.

[0026] The above description is a preferred embodiment of the present invention. For those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a perovskite solar cell based on NIC interface modification, characterized in that, The process is as follows: (1) Clean the FTO conductive glass and blow it dry to obtain a clean FTO conductive substrate; (2) A solution of titanium acetylacetonate in n-butanol was spin-coated onto a clean FTO conductive substrate, and after annealing, a dense TiO2 layer was obtained. (3) Dilute TiO2 slurry with anhydrous ethanol and spin-coat it onto a dense TiO2 layer. After annealing, a mesoporous TiO2 layer is obtained. (4) Spin-coating an ethanol solution of NIC onto a TiO2 mesoporous layer and annealing it to obtain a NIC-modified layer. The preparation process of the NIC ethanol solution is as follows: dissolve pyridine-3-carboxamide NIC in ethanol to obtain an ethanol solution with a concentration of 0.05~5 mg / mL NIC. (5) CH3NH3I and PbI2 are dissolved in a mixed solvent of DMF and DMSO to form a perovskite precursor solution, which is then spin-coated onto the NIC modified layer. Anhydrous diethyl ether is added as an anti-solvent during the spin-coating process. After spin-coating, the perovskite light-absorbing layer is obtained by annealing. (6) Spin-coating the Spiro-OMeTAD precursor solution onto the perovskite light-absorbing layer to obtain the hole transport layer; Spiro-OMeTAD precursor solution is prepared by mixing 72.3 mg of Spiro-OMeTAD powder, 28.8 μL of 4-tert-butylpyridine, and 17.5 μL of Li-TFSI salt solution per 1 mL of chlorobenzene. The Li-TFSI salt solution is an acetonitrile solution of Li-TFSI with a concentration of 500 mg / mL. (7) Place the sample obtained in step (6) into a desiccator for oxidation for 8 to 24 hours, and vacuum evaporate an Ag counter electrode on the hole transport layer. The thickness of the Ag counter electrode is 50 to 150 nm, thus obtaining a perovskite solar cell based on NIC interface modification.

2. The method for preparing a perovskite solar cell based on NIC interface modification as described in claim 1, characterized in that, In step (2), the concentration of the n-butanol solution of the titanium acetylacetonate is 0.1-0.5 mol / L, the annealing temperature is 80-150℃, and the annealing time is 5-30 minutes.

3. The method for preparing a perovskite solar cell based on NIC interface modification as described in claim 1, characterized in that, In step (3), the TiO2 slurry is a commercial slurry, and the TiO2 slurry and anhydrous ethanol are mixed evenly at a mass ratio of 1:(4~10); the annealing temperature is 450~550℃, and the annealing time is 50~70 minutes.

4. The method for preparing a perovskite solar cell based on NIC interface modification as described in claim 1, characterized in that, In step (4), the annealing temperature is 90~110℃ and the annealing time is 10~15 minutes.

5. The method for preparing a perovskite solar cell based on NIC interface modification as described in claim 1, characterized in that, In step (5), the concentration of CH3NH3I in the perovskite precursor solution is 1 mol / L, the concentration of PbI2 is 1.05 mol / L, the volume ratio of DMF to DMSO in the mixed solvent is 4:1, the annealing temperature is 80~150℃, and the annealing time is 20~40 minutes.

6. The method for preparing a perovskite solar cell based on NIC interface modification as described in claim 1, characterized in that, In step (7), the humidity of the dryer shall not exceed 10%.

7. The perovskite solar cell based on NIC interface modification prepared by the preparation method according to any one of claims 1 to 6.

8. The perovskite solar cell based on NIC interface modification as described in claim 7, characterized in that, The thickness of the TiO2 dense layer is 30~50nm, the thickness of the TiO2 mesoporous layer is 350~400nm, the thickness of the perovskite light-absorbing layer is 300~600nm, the thickness of the hole transport layer is 80~250nm, and the thickness of the Ag counter electrode is 50~150nm.

Citation Information

Patent Citations

  • Perovskite solar cell and preparation method thereof

    CN112490367A